Evaluation of survival outcomes in patients receiving palliative home parenteral nutrition: a retrospective observational study - Charlotte Rutter; Nicola Wilson; Dunecan Massey; Jeremy Woodward; Emma Mckenzie; Kristie Huirong Fan; Pinal S Patel; Rebecca Maddison (BMJ Open Gastroenterology)
Objective Intestinal failure in advanced malignancy is most commonly due to mechanical bowel obstruction. Palliative home parenteral nutrition (HPN) is an option for such patients to meet their nutritional needs. However, there are limited data on overall survival and predictive factors. This study aimed to evaluate the survival of patients receiving palliative HPN and the impact of patient factors on survival.Methods This is a single-centre retrospective observational study of patients referred for palliative HPN from 1 January 2020 to 19 November 2024 at the Cambridge University Hospitals NHS Foundation Trust. Demographic, nutritional and medical data were analysed. Survival rates were compared using Kaplan-Meier curves and Cox regression.Results 84 patients were referred and 77 were discharged with HPN (median age was 60.9 years (IQR: 51.3–70.4), female 77%). 78% of the underlying primary malignancies were gynaecological and gastrointestinal. Malignant bowel obstruction was the main indication for HPN (86%). Eastern Cooperative Oncology Group performance status (PS) scores were ≤2 in 82% of patients and 75% had an estimated prognosis of >3 months. Median survival was 58 days (IQR 31–108) with a 3-month mortality of 69%. There was no statistical difference in survival by PS, estimated prognosis, underlying malignancy or modified Glasgow Prognostic Score (mGPS).Conclusions The overall survival in our study is modest. PS, prognosis, mGPS or tumour type did not show a significant impact on survival. This highlights the challenges in artificial nutrition and emphasises the role of a multidisciplinary team in the care of these patients.